Peningkatan Hasil Belajar Matematika Melalui Model Pembelajaran Kooperatif Tipe Teams Games Tournament (TGT) Siswa Kelas XI di SMA Negeri 11 Makassar: Improving Mathematics Learning Outcomes Through the Cooperative Learning Model of Teams Games Tournament (TGT) Type for Grade XI Students at SMA Negeri 11 Makassar - Sukmawati, Sukmawati; Ja’faruddin, Ja’faruddin; Ahmad, Habriah (Jurnal Education, 2025)
This research is a type of classroom action research (CAR) which aims to improve students' mathematics learning outcomes through the application of PBL learning. The subjects in this study were students of class XI.4 at UPT SMA Negeri 11 Makassar consisting of 36 students. The instruments used to collect data included observation sheets of learning implementation, observation sheets of student activities and mathematics learning outcome tests. Data analysis was carried out using quantitative descriptive techniques using percentages. The results showed that the application of PBL learning models was able to improve students' mathematics learning outcomes. This can be seen from the percentage increase in learning outcomes from cycle I to cycle II, where in cycle I there were 17 students who achieved KKM (47.2%), while in cycle II the number increased to 31 students (86.11%).